"Two shots for life. HPV-vaccination at your school". Co-creation of a complex intervention to reduce ethnic inequity in childhood HPV-vaccination in Denmark. - Anne Katrine Leonhard; Sara Koed Badre-Esfahani; Mette Bach Larsen; Lone Kjeld Petersen; Lene Seibæk (PLoS ONE)
Despite free access to HPV-vaccination, adolescents with an ethnic minority background have an overall lower vaccination coverage due to various barriers needed to be accommodated in a targeted effort. We aim to report the development process of an intervention to increase HPV-vaccination coverage among adolescents with an ethnic minority background. An iterative co-creation guided by Medical Research Council UK development of complex interventions framework was done. We involved stakeholders throughout the process from the analysis of intervention interest and impact. The development process is described in four phases: 1) Evidence synthesis with focus-group interviews and literature review 2) Acceptability with stakeholders, 3) Elements and context with creation of a logic model, and finally 4) Co-production of material. The final intervention, "Two shots for life", is a school-based intervention consisting of HPV-education targeting adolescents and parents and HPV-vaccination at school during school hours. The intervention was designed to require the fewest possible resources for implementation sites, being municipality schools with a proportion of pupils >25% with ethnic minority background. Communication focus is HPV-vaccination as a prevention effort, it is mainly delivered face-to-face and written material is available in relevant minority languages as well as visual in appearance. A combined intervention with both educational and logistical components created with stakeholders is expected to accommodate barriers for HPV-vaccination in ethnic minority communities and increase accessibility and, hence, coverage of HPV-vaccination. By presenting a thorough development process, we expect to achieve transparency that will support future development of similar complex interventions aiming to increase HPV-vaccination coverage among ethnic minorities. ClinicalTrials.gov NCT05681169.